2017
DOI: 10.1111/1750-3841.13846
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and Its Relationship with the Molecular Characteristics of Food‐Related Methicillin‐Resistant Staphylococcus aureus (MRSA)

Abstract: In this study, some assayed isolates of food-related MRSA demonstrated the capacity to form biofilm. Biofilm formation differed according to surface characteristics and MRSA strains. A relationship was observed between some molecular characteristics and the ability to form biofilms. Few studies have investigated the ability of MRSA to form biofilms, and the majority of these studies have investigated clinical aspects. This work was performed to investigate whether or not there is a difference between MRSA food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
4
27
3
Order By: Relevance
“…The presented data of the DNA microarray analysis revealed that all S. aureus isolates harbored icaACD genes regardless of their origin. These results were in agreement with several findings made in human infections [46], human nasal samples [47], sheep mastitis [48], and isolates from food matrices [6].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presented data of the DNA microarray analysis revealed that all S. aureus isolates harbored icaACD genes regardless of their origin. These results were in agreement with several findings made in human infections [46], human nasal samples [47], sheep mastitis [48], and isolates from food matrices [6].…”
Section: Discussionsupporting
confidence: 92%
“…Here, the fnbB gene was rarely detected among non-biofilm-producing isolates but found in all biofilm-producing isolates from food matrices and humans. These findings were in discordance with a previous reports where either the fnbB gene was not detected in biofilm-producing isolates [6] or detected in a low level (29.0%) in MRSA isolated from humans [50]. However, a previous study reported that fnbB occurred frequently (99.5%) in S. aureus isolated from humans [46].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that all 52 S. aureus strains had different capability to adhere and form biofilm onto the tested hydrophobic surface. Similar observations were also reported by other investigators (Di Ciccio et al., ; Vergara et al., ). The ability of S. aureus to form biofilms on polystyrene surfaces may contribute to the persistence of the bacterium in food processing environments, thus highlighting this corresponding material as an important reservoir for S. aureus in the food sector.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, Fabres‐Klein et al., reported that biofilm production by bovine strains of S. aureus belonging to agr group 3 significantly increased in skim‐milk medium. Another study showed that the majority of milk and pork‐related MRSA biofilm‐producing strains belonged to agr group 3 (Vergara et al., ). Thus, the results from this study in combination with previous reported publications indicate that the analysis of biofilm formation by agr group 3 should be extended to more strains to substantiate the findings.…”
Section: Discussionmentioning
confidence: 99%